Length–weight Relationship and Condition Factor of Silver Pomfret (Pampus argenteus), Damanganga Estuary, Daman - Dubey , Monika; Koppar , B. J.; Singh , Vineet Prakash; Ahmed , Sana P Masood; Ujjania, N. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A study was conducted on the length-weight relationship and condition factor of the commercially important fish, Silver Pomfret (Pampus argenteus), in the Damanganga estuary in Daman. Fish samples were collected from January 2021 to March 2021, with a total of 330 randomly sampled fish collected from fishermen. The average total length was 23.309±0.775 cm and the average total weight was 259.606±20.144 grams measured using standard methods. The 'b' value of Pampus argenteus showed a negative allometric (b<3.0) growth pattern, with the total length being positively correlated with the total weight of the fish (r²=0.829). The growth pattern was negative allometric while the Fulton condition factor (2.03±0.114) indicated good condition. Therefore, further studies on the length-weight relationship should focus on the sustainable management of the fisheries.